Shellable Cactus Graphs - Mohammadi, Fatemeh; Kiani, Dariush; Yassemi, Siamak (Mathematica Scandinavica, 2010)
In this paper a new class of vertex decomposable graphs are determined. Moreover, all shellable and sequentially Cohen-Macaulay cactus graphs (i.e., connected graphs in which each edge belongs to at most one cycle) are characterized.